Surrendering authorial agency and practicing transindividualism in Tumblr's role-play communities - K. Shannon Howard (Transformative Works and Cultures, 2017)
The writer who engages in acts of online role-play or make-believe is often thought to promote him or herself as an individual agent. However, when members of Tumblr's role-play communities engage in play, they create scenes together that prompt surrender of authorial agency. In doing so, they engage in transindividual work, which allows them to work across, among, and between other entities until the boundaries of the self become porous rather than fixed.